Current status on treatment options for feline infectious peritonitis and SARS-CoV-2 positive cats. (1st January 2020) - Izes, Aaron M.; Yu, Jane; Norris, Jacqueline M.; Govendir, Merran
Abstract: Feline infectious peritonitis (FIP) is a viral-induced, immune-mediated disease of cats caused by virulent biotypes of feline coronaviruses (FCoV), known as the feline infectious peritonitis virus (FIPV). Historically, three major pharmacological approaches have been employed to treat FIP: (1) immunomodulators to stimulate the patient's immune system non-specifically to reduce the clinical effects of the virus through a robust immune response, (2) immunosuppressive agents to dampen clinical signs temporarily, and (3) re-purposed human antiviral drugs, all of which have been unsuccessful to date in providing reliable efficacious treatment options for FIPV. Recently, antiviral studies investigating the broad-spectrum coronavirus protease inhibitor, GC376, and the adenosine nucleoside analogue GS-441524, have resulted in increased survival rates and clinical cure in many patients. However, prescriber access to these antiviral therapies is currently problematic as they have not yet obtained registration for veterinary use. Consequently, FIP remains challenging to treat. The purpose of this review is to provide an update on the current status of therapeutics for FIP. Additionally, due to interest in coronaviruses resulting from the current human pandemic, this review provides information on domesticated cats identified as SARS-CoV-2 positive.